Does Secular Education Impact Religiosity, Electoral Participation and the Propensity to Vote for Islamic Parties? Evidence from an Education Reform in a Muslim Country - Resul Cesur; Naci Mocan (Koç University-TÜSİAD Economic Research Forum (ERF), 2014)
Using a unique survey of adults in Turkey, we find that an increase in educational attainment, due to an exogenous secular education reform, decreased women's propensity to identify themselves as religious, lowered their tendency to wear a religious head cover (head scarf, turban or burka) and increased the tendency for modernity. We also find that education has a negative impact on women's propensity to vote for Islamic parties. The impact of education on religiosity and voting preference is not working through migration, residential location or labor force participation. There is no statistically significant impact of education on men's tendency to vote for Islamic parties and education does not influence the propensity to cast a vote in national elections for either men or women.
Keywords: 330